Chemical qualitative analysis and spf value stability of nutmeg seed oil in microemulsions with tween 80 and PEG 400 as surfactants and cosurfactants - Ayu Shabrina; Erika Indah Safitri; Risha Fillah Fithria; Misbahul Munir; Sumantri Sumantri (Pharmaciana, 2022)
Nutmeg oil contains α-pinene, which can be used as sunscreen. The combination of Tween 80 and PEG 400 can maintain the stability of nutmeg oil microemulsion. This research was a follow-up study that aims to determine the stability of the SPF value and qualitative chemical content of nutmeg seed oil microemulsions (NSM). NSM was made with a nutmeg seed oil concentration of 6.4% and tween 80 and PEG 400 as surfactants and cosurfactants with variations in the ratio of F1 (5: 4), F2 (6: 4), and F3 (7: 4). Nutmeg seed oil and NSM content was analyzed using GC-MS. NSM formula were tested for in vitro SPF value stability by storing NSM in a climatic chamber at 30 °C ± 2 °C with RH 65 % ± 5 % for 4 weeks. The SPF values were calculated every week. GC-MS data were analyzed descriptively and data of SPF value stability were analyzed statistically using one way ANOVA. The GC-MS results of nutmeg seed oil showed 35 components, including significant compounds, namely α-pinene, sabinene, β-phellandrene and also α-terpinolene. GC-MS results of NSM showed those significant compounds were still detected after being formulated in microemulsion. The results of the sunscreen activity test of NSM before storage were 10.31 ± 0.03 (F1); 10.47 ± 0.07 (F2); 10.45 ± 0.03 (F3) and did not show significant change after storage for 4 weeks (p > 0.05). The SPF values of NSM were categorized in maximum activity.